2002
DOI: 10.1002/med.10005
|View full text |Cite
|
Sign up to set email alerts
|

Bioactive taxoids from the Japanese yew Taxus cuspidata

Abstract: A series of new taxoids, named taxuspines A-H and J-Z (1-25) and taxezopidines A-H and J-L (26-36), have been isolated together with 37 known taxoids (37-73) including paclitaxel (53) from the Japanese yew, Taxus cuspidata Sieb. et Zucc. (Taxaceae). These new taxoids possess various skeletons containing 5/7/6, 6/10/6, 6/5/5/6, 6/8/6, or 6/12-membered ring systems. Among the new taxoids, some non-taxol-type compounds remarkably reduced CaCl(2)-induced depolymerization of microtubules, or increased cellular accu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
24
0

Year Published

2005
2005
2010
2010

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(24 citation statements)
references
References 45 publications
0
24
0
Order By: Relevance
“…s), as well as the NOESY correlations of HÀC(3)/HÀC(7), HÀC(5)/H a ÀC(6), HÀC(5)/H b ÀC (6), and H b ÀC(6)/Me (19), indicated that the C-ring adopted a chair conformation. Further, the NOESY crosspeaks between HÀC(2)/HÀC(9), HÀC(2)/Me (19), HÀC(3)/HÀC(7), and HÀC(9)/ Me(19) indicated a trans junction of rings B and C. The b-orientations of HÀC(2), HÀC (9), and HÀC (13) were assigned on the basis of the NOESY correlations of HÀC(2)/HÀC(9), HÀC(2)/Me(17), HÀC(2)/Me (19), HÀC(9)/Me(17), HÀC(9)/ Me(19); and of HÀC(13)/H b ÀC (14), HÀC(13)/Me (16). The b-orientation of HÀC (5) was assumed from its small coupling constants with HÀC(4), H a ÀC (6), and H b ÀC(6) ( Table 1).…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…s), as well as the NOESY correlations of HÀC(3)/HÀC(7), HÀC(5)/H a ÀC(6), HÀC(5)/H b ÀC (6), and H b ÀC(6)/Me (19), indicated that the C-ring adopted a chair conformation. Further, the NOESY crosspeaks between HÀC(2)/HÀC(9), HÀC(2)/Me (19), HÀC(3)/HÀC(7), and HÀC(9)/ Me(19) indicated a trans junction of rings B and C. The b-orientations of HÀC(2), HÀC (9), and HÀC (13) were assigned on the basis of the NOESY correlations of HÀC(2)/HÀC(9), HÀC(2)/Me(17), HÀC(2)/Me (19), HÀC(9)/Me(17), HÀC(9)/ Me(19); and of HÀC(13)/H b ÀC (14), HÀC(13)/Me (16). The b-orientation of HÀC (5) was assumed from its small coupling constants with HÀC(4), H a ÀC (6), and H b ÀC(6) ( Table 1).…”
mentioning
confidence: 98%
“…The bb-, b-, and a-orientations of HÀC(2), HÀC(5), HÀC (9), and HÀC(10), respectively, were assumed from a biogenetic viewpoint of taxanes, and were in agreement with the observed coupling constants [14] [15]. Taking all these data into account, the structure of 2 was, therefore, unequivocally established as (2a,5a,9a,10b-)-2,9,10-triacetoxy-5-[(b-d-glucopyranosyl)oxy]-3,11-cyclotax-11-en-13-one.…”
mentioning
confidence: 99%
“…3. Structures of 3,11-cyclotaxanes type taxane was markedly different from those of other taxanes, especially with respect to the coupling constants between HÀC(9) and HÀC (10). On the other hand, a set of AB system of H a ÀC (16) Fig.…”
Section: 144mentioning
confidence: 92%
“…The biological data of taxuspine U are not yet published but it is well known that taxuspine X is able to increase accumulation of vincristine in MDR cell lines, so it is interesting for overcoming multi-drug resistance. 17 Interestingly this compound is characterized by a cinnamoyl group at C-5, while lacking both an oxetane ring and a phenylisoserine group at C-13. Once fitted into the tubulin binding site, the closely resemblance of taxuspine U 3D rearrangement to taxol bioactive conformation led us to design few structural modification of 22 ( Figure 6, A), aimed at obtaining interesting molecule, such as 24 ( Figure 5), potentially active as anticancer and/or MDR reversing agents.…”
mentioning
confidence: 99%